2021
DOI: 10.1111/gove.12645
|View full text |Cite
|
Sign up to set email alerts
|

Government information disclosure and citizen coproduction during COVID‐19 in China

Abstract: While information campaigns have been widely recognized as a pillar of public health crisis management and heightened by the current COVID‐19 pandemic, an insufficient number of studies have investigated the impact of information disclosure on influencing citizen cooperation crucial for emergency management. Focusing on generic information disclosure practices during the recovery period from January 19, 2020, to February 29, 2020, in China and by employing a difference‐in‐difference method, this study finds th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 50 publications
1
19
0
Order By: Relevance
“…More importantly, after controlling for areas and education level of participants, our study showed the emotion of optimism, concerns about the COVID-19 pandemic, perceived efficiency, and transparency of the government in releasing COVID-19 relevant information positively predicted confidence in fighting COVID-19, while anger negatively predicted confidence in fighting COVID-19. The positive role of the transparent communication of the government on the public trust and attitudes toward the control measures was also suggested in previous studies [ 53 , 54 , 55 ]. For example, research on COVID-19 pandemic lockdowns suggested that the perceived capability of the government positively affected public confidence and policy effectiveness [ 53 ].…”
Section: Discussionsupporting
confidence: 66%
“…More importantly, after controlling for areas and education level of participants, our study showed the emotion of optimism, concerns about the COVID-19 pandemic, perceived efficiency, and transparency of the government in releasing COVID-19 relevant information positively predicted confidence in fighting COVID-19, while anger negatively predicted confidence in fighting COVID-19. The positive role of the transparent communication of the government on the public trust and attitudes toward the control measures was also suggested in previous studies [ 53 , 54 , 55 ]. For example, research on COVID-19 pandemic lockdowns suggested that the perceived capability of the government positively affected public confidence and policy effectiveness [ 53 ].…”
Section: Discussionsupporting
confidence: 66%
“…Second, CPPCM, which is an essential component of ideal risk communication, was able to create a consensus among residents, promote citizen policy compliance, and increase citizen cooperation during COVID-19 [ 53 ]. Regarding citizen compliance and collective cooperation in emergencies, it is impossible to control a pandemic [ 54 ] without citizen compliance and voluntary cooperation [ 55 ], such as maintaining social distance and receiving a vaccination. Additionally, PPP may require social forces to participate in pandemic prevention actions to form a type of collaborative governance.…”
Section: Discussionmentioning
confidence: 99%
“…Only by seeing the full picture of the real situation can volunteers try to help others in need and take care of themselves. Therefore, optimal risk information communication strategies that considering multiple elements are imperative, aiming at reducing the public's risk perception without misleading risk information during a crisis instead of shutting the public away from risk information ( 68 , 69 ).…”
Section: Discussionmentioning
confidence: 99%